Hydrogeochemical Characterization Using Piper Diagram of the Groundwater Surrounding the Wild Dump of the El Hajeb Town, Morocco - Abderrahmane Gamar; Zakaria Khiya (Journal of Advances in Environmental Health Research)
Background: The availability of groundwater with acceptable quality has become a significant challenge in many regions worldwide, particularly in Morocco. This issue is exacerbated by severe climatic conditions and pollution, which render groundwater resources increasingly vulnerable to various contamination factors. The Plateau of the El Hajeb region is part of the Causse Middle Atlas and the water table of the grand basin of Saïs, two major main reservoirs of groundwater in Morocco. In this context, the primary aim of this study is to identify the geochemical facies of the groundwater in the region housing the municipal waste dump. Additionally, the study seeks to determine the sources of mineralization affecting these waters. Methods: Over the course of two sampling campaigns conducted between 2015 and 2018, groundwater samples were collected from 97 points. These points were strategically located around the municipal waste dump and along the groundwater flow, including wells, boreholes, and springs. Analyses were conducted in accredited laboratories following standardized methods, with a focus on the determination of major ions. Results: The results of the geochemical analysis, as represented by the Piper diagram, revealed a calco-bicarbonate facies with low mineralization. This low mineralization does not affect the potability of the waters, thus maintaining their suitability for human consumption. The carbonate formations (calcite and dolomite) constitute the host rocks of the groundwater. Conclusion: Chlorination and/or sulfation alteration processes were observed, contributing to the presence of specific ionic species associated with anthropogenic pollution.